Разработка технологии ржано-пшеничных хлебобулочных изделий, обогащенных инулином - Костюченко, Марина; Мартиросян, Владимир; Моисеенко, Александра; Щербаков, Павел (ՀԱԱՀ հիմնադրամ)
Հոդվածում ներկայացված են գետնախնձորի ալյուրի օգտագործմամբ աշորացորենային հացաբուլկեղենի արտադրության տեխնոլոգիայի մշակման նպատակով իրականացված հետազոտության արդյունքները: Գետնախնձորի ալյուրն ավելացվել է խմորի հունցման փուլում՝ ալյուրի ընդհանուր զանգվածի 7-10 %-ի չափով։ Գետնախնձորի ալյուրի օգտագործումը նպաստել է հացաբուլկեղենի սննդային արժեքի բարձրացմանը եւ հնացման արագության նվազման շնորհիվ պահպանման ժամկետի երկարացմանը: Գետնախնձորի ալյուրի 10 % չափաբաժնի դեպքում ստուգիչ՝ առանց հավելումների տարբերակի համեմատությամբ նկատվել է պատրաստի արտադրանքի զգայաբանական եւ ֆիզիկաքիմիական ցուցանիշների վատթարացում։ Ըստ հետազոտության արդյունքների՝ գետնախնձորի ալյուրի ավելացման օպտիմալ քանակությունը պետք է կազմի ալյուրի ընդհանուր զանգվածի 7 %-ը: The most effective way to improve the population's diet is through the development and industrial production of functional food products, enriched with essential nutrients. This article presents research focused on developing the technology for rye-wheat bakery products incorporating Jerusalem artichoke flour. Jerusalem artichoke flour was added during the dough kneading stage in amounts ranging from 7 % to 10 % of the total flour weight. The inclusion of Jerusalem artichoke flour resulted in a slower staling rate of the bakery products during storage, thus extending their shelf life. In bread without additives, the staling rate was 2.10 N/day, while the addition of Jerusalem artichoke flour at 7 % and 10 % reduced the staling rate to 1.56 N/day and 0.86 N/day, respectively. However, increasing the Jerusalem artichoke flour dosage to 10 % led to a decline in the organoleptic properties of the final product, with a 9% reduction in bread volume, a 7 % decrease in crumb porosity, a 46% increase in crumb hardness, and an 82 % increase in crumb crumbliness, compared to the control sample without additives. Based on the results, the optimal amount of Jerusalem artichoke flour was determined to be 7 % by weight of flour in the dough. The use of Jerusalem artichoke flour primarily contributed to enriching the bakery products with inulin. It was found that with 7 % Jerusalem artichoke flour by weight of flour, 100 g of the bakery product contained 5.8 g of dietary fiber, 2.8 g of inulin, 41.9 mg of magnesium, 150.0 mg of phosphorus, 15 mg of iron, and 0.73 μg of selenium. The developed baked goods enriched with Jerusalem artichoke flour are functional food products that provide inulin, dietary fiber, and phosphorus, with a low fat content․
Keywords: Продовольственная наука и пищевые технологии